Features of legal regym of aviation transport lands - Хом'яченко, Світлана Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In article the author analyzes norms of the current legislation concerning the air transport lands that inaggregate make a legal regime of the lands of an air transport in general and the lands under the airports (airdromes) in particular as basic making serving infrastructure of an air transport.